THE REPRESENTATION OF THE ANCIENT SOGDIAN STATE IN WRITTEN SOURCES - Poyonov Ixtiyor Abdimo'min o'g'li (World Scientific Research Journal, 2025)
Annotation. This article provides a brief overview of the Ancient Sogdian state, including when it was founded and the territories it encompassed. It also discusses the socio-economic structure and economic life of its ancient cities. Furthermore, the article presents concise information derived from the accounts of ancient Greek scholars and the findings of modern scientific research conducted on the Ancient Sogdian state.